Connections Between the Mass Balance, Ice Dynamics, and Hypsometry of White Glacier, Axel Heiberg Island, Nunavut - Thomson, Laura Irene (Université d'Ottawa / University of Ottawa, 2016)
This thesis investigates how changing climate conditions have impacted the mass balance, dynamics and associated hypsometry (area-elevation distribution) of White Glacier, an alpine glacier on Axel Heiberg Island, Nunavut. The first article describes the production of a new map of White Glacier from which changes in ice thickness and glacier hypsometry could be determined. A new digital elevation model (DEM) was created using >400 oblique air photos and Structure from Motion, a method built upon photogrammetry but with the advantage of automated image correlation analysis. The result of this work demonstrates that the method is able to overcome the challenges of optical remote sensing in snow-covered areas. The resulting DEM and orthoimage facilitated the production of a map with 5 m vertical accuracy in the style of earlier cartographic works. The new map supported the calculation of the glacier’s geodetic mass balance and provides an updated glacier hypsometry, which improves the accuracy of mass balance calculations. A modeled glacier hypsometry time-series was created to support a reanalysis of the mass balance record over the period 1960-2014, which through comparison of the geodetic and glaciological methods enables the detection of potential sources of error in the glaciological method. Comparison of the two approaches reveals that within the error margin no significant difference exists between the average annual glaciological mass balance (-213 ± 28 mm w.e. a 1) and geodetic mass balance ( 178 ± 16 mm w.e. a-1). To determine how ice dynamics have responded to ice thinning and negative mass balances, dual-frequency GPS observations of ice motion were compared to historic velocity measurements collected at three cross-sectional profiles along the glacier. Comparisons of annual and seasonal velocities indicate velocity decreases of 10–45% since the 1960s. However, increased summer velocities at the highest station suggests that increased delivery of surface meltwater to the glacier bed has initiated basal sliding at elevations that did not experience high levels of melt in earlier decades. Modeled balance fluxes demonstrate that observed fluxes, both historically and currently, are unsustainable under current climate conditions.
Keywords: glacier; Arctic; ice dynamics; mapping; mass balance; climate